2013
DOI: 10.2466/16.02.pr0.113x30z2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Trauma Characteristics as Predictors of Attrition from Cognitive-Behavioral Therapy for Child Victims of Violence

Abstract: Little research has investigated psychotherapy attrition among child victims of violence, and no studies have evaluated the role of trauma characteristics (e.g., level of threat or injury, trauma frequency, perpetrator relationship, victim type, and trauma type). The current study evaluated premature psychotherapy termination with 134 child victims (ages 5-19 years) who were referred for exposure-based cognitive-behavioral therapy. Results indicated that premature treatment termination was associated with chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 55 publications
(67 reference statements)
1
14
1
Order By: Relevance
“…Number of traumatic events was also unrelated to both attrition definitions, in contrast to prior work that reported that a greater number of traumas predicted risk for clinician-rated treatment dropout, but not adequate dose status (Author citation; Author citation). However, one study observed that fewer traumatic events corresponded with attrition (Chasson et al, 2013). It is possible that there are subgroups of trauma-exposed families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Number of traumatic events was also unrelated to both attrition definitions, in contrast to prior work that reported that a greater number of traumas predicted risk for clinician-rated treatment dropout, but not adequate dose status (Author citation; Author citation). However, one study observed that fewer traumatic events corresponded with attrition (Chasson et al, 2013). It is possible that there are subgroups of trauma-exposed families.…”
Section: Discussionmentioning
confidence: 99%
“…Aspects of the traumatic event have also been investigated as potential risk factors for attrition. A few studies have observed that experiencing a greater number of traumas was related to increased risk for clinician-rated treatment attrition (Author citation; Author citation; Jensen et al, 2014); however, one study found that exposure to fewer traumas was tied to dropout (Chasson, Mychailyszyn, Vincent, & Harris, 2013). Complex trauma, defined as chronic interpersonal trauma that began early in life, was also unrelated to premature termination (Author citation).…”
mentioning
confidence: 99%
“…Regression analyses were used in four 482,630,631,633 studies to examine treatment completion. Caregivers' perceptions of the severity of abuse appear to be a common theme relating to treatment completion.…”
Section: Treatment Completionmentioning
confidence: 99%
“…Chasson et al 482 reported that higher levels of depressive symptoms and feelings of intrusion during treatment were associated with dropout from TF-CBT. In a later study, 630 in which they analysed data from the same group of children augmented with additional cases, the authors found that children who had been abused by another child (not by a parental/adult figure), or had experienced a single event and had not suffered a life-threatening or serious injury, were more likely to drop out than those children exposed to multiple, physical injurious abuse by an adult. Eslinger et al 631 found that the odds of dropout were greater for children with younger parents.…”
Section: Treatment Completionmentioning
confidence: 99%
See 1 more Smart Citation